2018
DOI: 10.3390/mi9120618
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocatalytic Performance of Nitrogen-Doped TiO2 Nanotube Arrays Using a Simple Annealing Process

Abstract: Nitrogen-doped TiO2 nanotube arrays (N-TNAs) were successfully fabricated by a simple thermal annealing process in ambient N2 gas at 450 °C for 3 h. TNAs with modified morphologies were prepared by a two-step anodization using an aqueous NH4F/ethylene glycol solution. The N-doping concentration (0–9.47 at %) can be varied by controlling N2 gas flow rates between 0 and 500 cc/min during the annealing process. Photocatalytic performance of as-prepared TNAs and N-TNAs was studied by monitoring the methylene blue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…Also, there were no rutile peaks, indicating that the TiO 2 nanomaterials in this study possessed a pure anatase phase. This result agreed with those reported in [4,5,13,19,48,49]. A closer inspection of the (004) peaks revealed that Au (111) component was found in the (004) peaks of Au-TNAs and Au-TNWs/TNAs, as demonstrated in Figure 1c, confirming the presence of crystalline Au NPs in these samples.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Also, there were no rutile peaks, indicating that the TiO 2 nanomaterials in this study possessed a pure anatase phase. This result agreed with those reported in [4,5,13,19,48,49]. A closer inspection of the (004) peaks revealed that Au (111) component was found in the (004) peaks of Au-TNAs and Au-TNWs/TNAs, as demonstrated in Figure 1c, confirming the presence of crystalline Au NPs in these samples.…”
Section: Resultssupporting
confidence: 92%
“…During the anodization process, TNA growth is driven by the anodic-oxidation reaction (to form TiO 2 from Ti) and the chemical dissolution of the TiO 2 layer under the presence of electric field [19,51,52,53]. The reactions are given below:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected the aquaculture wastewater samples with high antibiotic concentrations, including OTC (CM-DD 5 , 112.6 ng•mL −1 ), DXC (AG-CT 8 , 55.6 ng•mL −1 ), SMX (CM-DD 9 , 83.5 ng•mL −1 ), SMZ (AG-CT 2 , 48.4 ng•mL −1 ), and LCM (BL-HB 4 , 60.7 ng•mL −1 ) to study photocatalytic degradation of the antibiotics by TNAs and TNWs/TNAs under UV-VIS exposure at various reaction times of 0, 5, 9, 14, and 20 min. The pseudo-first-order rate constants were determined by fitting the data with the Langmuir-Hinshelwood kinetics rate model [63,79]. Figure 4a,b show the photocatalytic degradation kinetic of LCM, DXC, OTC, SMZ, and SMX using TNAs and TNWs/TNAs under UV-VIS irradiation.…”
Section: Photocatalytic Degradation Of Antibiotics In Aquaculture Wasmentioning
confidence: 99%
“…Antibiotics are widely used for treatment and prevention of infectious diseases in humans and in domestic and food-producing animals, including fish [1,2]. The use and overuse of antibiotics in aquaculture is of great concern because it may cause antibiotic residues in aquatic environments and and non-toxicity [46,47,[60][61][62][63][64]. In this study, TiO 2 nanotube arrays (TNAs) and TiO 2 nanowires on nanotube arrays (TNWs/TNAs) are of interest because they can provide a large surface-to-volume ratio and unidirectional electrical channel [65,66].…”
Section: Introductionmentioning
confidence: 99%